Role of Spasticity Severity in the Balance of Post-stroke Patients - Mahmoudzadeh, Ashraf; Nakhostin Ansari, Noureddin; Naghdi, Soofia; Ghasemi, Ehsan; Motamedzadeh, Omid; Shaw, Brandon S.; Shaw, Ina (Frontiers in Human Neuroscience, 2021)
Background: Lower limb spasticity after stroke is common that can affect the balance, increase the risk of falling, and reduces the quality of life. Objective: First, evaluate the effects of spasticity severity of ankle plantar flexors on balance of patients after stroke. Second, to determine the relationship between the spasticity severity with ankle proprioception, passive ankle dorsiflexion range of motion (ROM), and balance confidence. Methods: Twenty-eight patients with stroke based on the Modified Modified Ashworth Scale (MMAS) were divided into two groups: High Spasticity Group (HSG) (MMAS>2) (n=14) or a Low Spasticity Group (LSG) (MMAS≤2) (n=14). The MMAS scores, Activities-Specific Balance Confidence Questionnaire, postural sway of both affected and nonaffected limbs under the eyes open and eyes closed conditions, timed up and go (TUG) test, passive ankle dorsiflexion range of motion (ROM), and ankle joint proprioception were measured. Results: The ankle joint proprioception was significantly better in the LSG compared to the HSG (p=0.01). No significant differences were found between the LSG and HSG on all other outcome measures. There were no significant relationships between the spasticity severity and passive ankle dorsiflexion ROM, and balance confidence. Conclusions: The severity of ankle plantar flexor spasticity had no effects on balance of patients with stroke. However, the ankle joint proprioception was better in patients with low spasticity. Our findings suggest that the balance is affected regardless of the severity of the ankle plantar flexor spasticity in this group of participants with stroke.